Integrating Miranda Rights to Promote Human Rights Compliance - Saraswati, Sekarwangi; Olim Narzullayev (Lembaga Contrarius Indonesia, 2025)
Despite the Indonesian Constitution recognizing the rule of law and Indonesia’s ratification of several international human rights treaties, the actual protection of suspects’ rights within criminal proceedings remains weak, largely because the provisions are declarative and poorly enforced. This research examines the possibility of incorporating Miranda Rights into the Indonesian legal framework as a means to improve adherence to global human rights standards. The research applies a normative juridical method with a conceptual approach, drawing upon statutory analysis and a comparative review of the United States criminal justice system. Findings reveal a persistent discrepancy between legal norms and their implementation, reflected in ongoing practices of torture and infringements on the rights to silence and legal counsel. While certain aspects of Miranda principles are embedded in the Criminal Procedure Code, explicit regulations requiring Miranda Warnings, as mandated in the United States, are absent. As a result, the safeguarding of suspects’ rights continues to rely heavily on the discretion of law enforcement officers, leaving significant room for abuse. Integrating Miranda Rights into Indonesia’s legal system is therefore a strategic reform to strengthen the protection of human rights in criminal justice. Such integration would enhance the credibility of law enforcement, deter torture, and align national practices with international obligations, especially the ICCPR’s fair trial guarantees. Ultimately, Miranda Rights offer a concrete tool to foster a more humane, transparent, and equitable justice system.